2015
DOI: 10.1109/tbcas.2015.2492460
|View full text |Cite
|
Sign up to set email alerts
|

A Bio-Inspired AER Temporal Tri-Color Differentiator Pixel Array

Abstract: This article investigates the potential of a bio-inspired vision sensor with pixels that detect transients between three primary colors. The in-pixel color processing is inspired by the retinal color opponency that are found in mammalian retinas. Color transitions in a pixel are represented by voltage spikes, which are akin to a neuron's action potential. These spikes are conveyed off-chip by the Address Event Representation (AER) protocol. To achieve sensitivity to three different color spectra within the vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Lichsteiner et al [32] introduced the concept of an Address-Event Representation (AER) silicon retina chip capable of generating events proportional to the log intensity changes. Farian et al [33] proposed an in-pixel colour processing approach inspired by the retinal colour opponency, using the same AER concept. Brandli et al [34] proposed a new version of the AER camera reported by Lichsteiner [32] called the dynamic, active pixel vision sensor (DAVIS), which exploits the efficiency of the AER protocol and introduces a new synchronous global shutter frame concurrently.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lichsteiner et al [32] introduced the concept of an Address-Event Representation (AER) silicon retina chip capable of generating events proportional to the log intensity changes. Farian et al [33] proposed an in-pixel colour processing approach inspired by the retinal colour opponency, using the same AER concept. Brandli et al [34] proposed a new version of the AER camera reported by Lichsteiner [32] called the dynamic, active pixel vision sensor (DAVIS), which exploits the efficiency of the AER protocol and introduces a new synchronous global shutter frame concurrently.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Color: Most diurnal animals have some form of color vision, and most conventional cameras offer color sensitivity. Early attempts at color sensitive event cameras [86], [87], [88] tried to use the "vertacolor" principle of splitting colors according to the amount of penetration of the different light wavelengths into silicon, pioneered by Foveon [89], [90]. However, it resulted in poor color separation performance.…”
Section: Advanced Event Camerasmentioning
confidence: 99%

Event-based Vision: A Survey

Gallego,
Delbruck,
Orchard
et al. 2019
Preprint
“…The excellent temporal resolution of DVSs has made possible to track fast movements of particles in fluids, reducing the data throughout Color change detection . Combining the pixel architecture of a DVS with stacked photodiodes at different depths in standard silicon, it was possible to create an image sensor whose pixels only react to color changes (transient shifts within the spectrum). Stereo vision .…”
Section: Dynamic Vision Sensorsmentioning
confidence: 99%